KAJIAN KERUSAKAN LAHAN SUB DAS KEDUANG DI GUNUNG KENDENG DI DESA NGADIPIRO, KECAMATAN NGUNTORONADI, KABUPATEN WONOGIRI - Winarno, Joko (Caraka Tani: Journal of Sustainable Agriculture, 2009)
The study site is administratively located at Ngadipiro village, Nguntoronadi subdistrict, Wonogiri regency with the total area of 663.61 ha. The coordinate of the study site lies at latitude of 7o52â€™00â€ â€“ 7o54â€™15â€ S and longtude of 110o57â€™45â€ â€“ 111o60â€™45â€ E and altitude of 196-427 m a.s.l. According to geomorphologic, the study site is a denudation hilly area, which severely scraped, with the type of primary land use is rainfed, which occupied by annual crops and seasonal crops. This reaserch were aimed at: 1) identify the physical problems and soil cultivation that have caused the land degradation; 2) obtain the alternative solutions for land degradation, which is suitable with the land physical condition. The type of this research is phenomenology description, with the method of surveying. Land mapping technique used the overlay of three maps, i.e: slope map, soil depth map and land use map, which is obtained from the interpretation of topographic map with the scale of 1:25.000. The obtained land unit was used for analysis unit. The land evaluation was carried out based on: 1) observations of land degradation indicators (land cover, outcrop, soil erosion, soil slide, bench erosion and soil depth); 2) soil erosion analysis with USLE formula, which described by soil hazard class. The alternative solution were based on the land degradation types, the threat levels of land degradation and the land management by farmers. Conclusions: physical problems found are: 1) the climate conditions promoted physical and chemical rocks weathering; 2) the volume of eroded soil corresponded to slope, which shaped â€œSâ€; soil management problem found are: 1) land management by farmers also could drive the land degradation, 2) the low level of farmers economical condition resisted the adoption of technology innovation by farmers. The alternative solution offered are minimum soil tillage (TOT) at 9, 10, 11 and 12 land units. On the other hand, the land units of 2, 3, 6, 7, 9, 10 and 12 required the roraks construction and the planting of cover crops and annual crops periodically.